Case report: Blotchy skin in a puffy neonate: is there a new association? - Joseph, Chacko J.; Lodha, Arijit; Thomas, Soumya R.; Al Awad, Essa; Wright, Nicola A. M.; Constantinescu, Cora; Le, Doan; Kamaluddeen, Majeeda (Frontiers in Pediatrics, 2023)
Introduction Purpura fulminans in the neonatal population is a rare but potentially life-threatening condition complicated by thrombosis, resultant vital organ necrosis, and gangrene of the extremities. Considering the rapid evolution of the pathogenetic mechanism, an index of suspicion, early identification, and prompt intervention are imperative for improved outcomes. The majority of purpura fulminans cases have an infectious etiology, but it is essential to consider other congenital and acquired causes. Case description We present a clinical case of a female neonate to emphasize the correlation between purpura fulminans, congenital chylothorax, involvement of the PAK2 gene, and the occurrence of retinal detachment in both eyes. After draining the congenital chylothorax, the neonate developed purpura fulminans due to a loss of protein C, S, and antithrombin factors, previously not reported in the literature. The purpuric lesions resolved after the administration of fresh frozen plasma. Subsequently, no recurring purpura fulminans lesions were noted following the normalization of the antithrombotic factor levels in the serum. Subsequently, the child also developed retinal detachment in both eyes.